A comparative study of satellite altimetry-based and DEM-based methods for estimating lake water volume changes - Haotian Li; Jun Chen; Liguo Cao; Wei Liu; Zheng Duan (Water Science and Technology, 2024)
This study compared two different methods, the satellite altimetry-based and DEM (digital elevation model)-based, for estimating lake water volume changes. We focused on 34 lakes in China as the testing sites to compare the two methods for lake water volume changes from 2005 to 2020. The satellite altimetry-based method used water levels provided by the DAHITI (Database for Hydrological Time Series of Inland Waters) data and surface areas derived from Landsat imagery. The DEM-based method used the SRTM DEM data in combination with Landsat-derived lake extents. Our results showed a high degree of consistency in lake water volume changes estimated between the two methods (R2 > 0.90), but each method has its limitations. In terms of temporal coverage, the satellite altimetry-based method with the DAHITI data is limited by missing water level data in certain periods. The performance of the DEM-based method in extracting lake shore boundaries in regions with flat terrains (slope <1.5°) is not satisfactory. The DEM-based method has complete regional applicability (100%) in the Tibetan Plateau (TP) Lake Region, yet its effectiveness drops significantly in the Xinjiang and Eastern China Plain Lake Regions, with applicability rates of 50 and 40%, respectively. HIGHLIGHTS Although the water volume changes derived from these methods are highly consistent, the two methods are still affected by different constraints.; The limitations and regional applicability of the two methods were analyzed in detail.; The DEM method is more suitable for estimating lake water volumes in the Tibetan Plateau Lake Region, and the DAHITI method is suitable for lakes with complete water level data.;